Організація педагогічного експерименту з розвитку лідерського потенціалу студентів в умовах інформаційного суспільства - Резнік, Світлана Миколаївна (Класичний приватний університет, 2017)
У статті проаналізовано організацію педагогічного експерименту з розвитку лідерського потенціалу студентів в умовах інформаційного суспільства. Педагогічний експеримент включав три етапи: констатувальний, формувальний, порівняльний. Результати експерименту продемонстрували, що розроблена психолого-педагогічна програма значним чином впливає на розвиток лідерського потенціалу студентів вищого технічного навчального закладу.

The article contains the analysis of a pedagogic experiment on leadership potential development in students within information society. 417 students and 18 teachers took part in the experiment. The methods of research were questionnaire polls, observation, sample interviews, testing, expert estimations method, and self-evaluation. At the initial stage of the experiment there was performed the analysis of the level of leadership potential development in students under conditions of traditional system of the study process organization. The results analysis of the stating experiment proved the assumption that the present system of training at higher education establishments is not effective enough in students’ leadership potential formation. The following stage in the research was the formal experiment whose aim was to substantiate, develop, and verify a psychological-and-pedagogic program of leadership potential development in students of a technical higher education establishment. The program was introduced into the training process for students of the experimental group, while students in the reference group were trained by traditional methodology. After the experiment was over, the students in the experimental group displayed a considerably higher level of leadership potential formation than those in the reference group. Thus, in the experimental group the number of students with a high level of the mentioned factor’s formation has changed approximately by one-third (15.7 % growth) than that in the reference group (4.9 % growth). The number of students with low level of the viewed factor formation has decreased in the experimental group by 23.4 %, while in the reference group by 10.7 %. The results of the comparative experiment have demonstrated that the developed psychological-and-pedagogic program considerably influences the development of leadership potentials in students of a technical higher education establishment.
Organization of pedagogic experiment on leadership potential development in students within information society
Keywords: лідерський потенціал; педагогічний експеримент; етапи педагогічного експерименту; leadership potential; pedagogic experiment